INTERNALIZATION OF RELIGIOUS AND CULTURAL VALUES AS CAREER GUIDANCE CONTENT FOR URBAN AND RURAL MUSLIM STUDENTS’ - Ashadi Cahyadi; Muhammad Nikman Naser; Ahmad Siddiq Ridha; Rahmat Alfianzah; Bayu Mitra A Kusuma (Akademika : Jurnal Pemikiran Islam, 2023)
The career development tasks of urban and rural Muslim students tend to experience obstacles, especially when they are in the final semester of college. This situation and condition needs to be addressed responsively by educators and managers of career development centers in every Islamic university in particular. Various approaches have been taken in an effort to facilitate student career development, but the limited content of career guidance has not maximized religious and cultural values systematically and comprehensively. The purpose of this study is to describe the career guidance model and examine cultural values and religion in several PTKI in the Sumatra region. The method in this research uses a qualitative approach and is analyzed using descriptive methods and content analysis. The process of collecting data through interviews and analyzing data triangulation by comparing some field findings to expert informants. The results of this study found several religious and cultural values that can be used as content or discussion themes in the career guidance process. The results of this study found that religious values related to career or one's success are listed in QS Al-Ahzab: 70, At-Taubah: 105, An-Nahl: 78, HR. Ahmad Ibnu Abid Dunya, Ath-Thabrani, & Al-Baihaqi, HR Tirmidzi and Al- Hakim. Some cultural values that can be the content of career guidance are related to the values of honesty, enthusiasm for learning, hard work, adaptation, and understanding of human weaknesses and strengths.